Analisis Hubungan antara Pengetahuan, Afeksi dan Komitmen terhadap Lingkungan - Selviranti, Selviranti; Sihombing, Sabrina O (Akutansi Bisnis & Manajemen ( ABM ), 2007)
The purpose of thus research is to investigate the relationship between ecological knowledge, consumer affection and commitment. A self-administered questionnaire war distributed to respondents by the drop-off / pick-up method, resulted 150 respondents. Data was analyzed by using structural equation modeling. The results supported all research hypotheses. The paper provides the implications for theoretical and managerial and offer directions for future research.